Sustainable alginate lyases catalyzed degradation of bio-based carbohydrates - Zheng, Zhiguo; Dai, Ali; Liu, Yonggui; Li, Tingting (Frontiers in Chemistry, 2022)
Alginate is a water-soluble and acidic polysaccharide derived from the cell wall and intercellular substance of brown algae. It is widely distributed in brown algae, such as Laminaria, Sargassum, and Macrocystis, etc. Alginate lyase can catalytically degrade alginate in a β-eliminating manner, and its degradation product-alginate oligosaccharide (AOS) has been widely used in agriculture, medicine, cosmetics and other fields due to its wide range of biological activities. This article is mainly to make a brief introduction to the classification, source and application of alginate lyase. We hope this minireview can provide some inspirations for its development and utilization.